Increasing equitable access to telehealth oncology care in the COVID‐19 National Emergency: Creation of a telehealth task force. (10th October 2022) - Worster, Brooke; Waldman, Lauren; Garber, Gregory; Zhan, Tingting; Lopez, AnaMaria; Trachtenberg, Olivia; Handley, Nathan; Rising, Kristin L.; Csik, Valerie; Leader, Amy
Abstract: Introduction: Telehealth (TH) utilization in cancer care prior to COVID‐19 was variable. Research highlights disparities in access determined by socioeconomic factors including education, income, race, and age. In response to COVID‐19 and these disparities, we assessed the impact of a personalized digital support structure, the Telehealth Task Force (TTF), to reduce disparities in TH. Methods: We performed a retrospective review of cohorts between January 1, 2020 and August 30, 2020: Pre (TH use with basic telephone support), Intervention (TH access with TTF), and Post (TH access after TTF initiation and educational material dissemination). Data collected included successful TH access, health literacy (HL), and Area Deprivation Index, a ranking of neighborhoods by socioeconomic disadvantage (ADI). The data were analyzed in univariate ordinary least squares model and adjacent categories ratio model using statistical software R to understand the relationship between TTF, HL, ADI, and TH access. Results: We included 555 patients from January 1, 2020 to August 30, 2020 (90 preintervention, 194 intervention, and 271 postintervention), excluding patients without ADI/HL. TTF support successfully engaged older, racially, and socioeconomically diverse patients in TH; ADI is significantly higher in the postintervention group vs. preintervention (mean difference = 7.66, 95% CI 1.00–4.32, p  = 0.024) and more patients had low HL during intervention compared with preintervention (adjacent categories ratio = 0.62, 95% CI 0.41–0.93, p  = 0.021). Discussion: COVID‐19 created an immediate need for TH. Implementation of the TTF helped close the digital divide, increasing TH access for vulnerable patients. Attention to digital readiness can mitigate disparities in access to care. Future research should explore the implementation of widespread routine digital support initiatives. Abstract : In response to COVID‐19 and disparities in access determined by socioeconomic factors, we assessed the impact of a personalized digital support structure, the Telehealth Task Force (TTF), to reduce disparities in TH. Implementation of the TTF helped close the digital divide; increasing TH access for vulnerable patients. Attention to digital readiness can mitigate disparities in access to care.